An efficient One-Time Password authentication scheme using a smart card. (22nd July 2009) - Lee, Sookyoung; Sivalingam, Krishna M.
This paper presents a One-Time Password (OTP) mechanism to provide authentication, with particular application to thin clients in wireless networks. Many of the current OTP mechanisms have high client side computation costs, high communication costs, or limited login times. To cope with these problems, this paper proposes a new one-time password scheme using a smart card. In the scheme, we present a novel modification to the Depth-First Search (DFS) based on a unique tree structure to generate a private key. We present a detailed analysis of the proposed scheme using an OpenSSL based implementation.